(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2023)
The seed is a vehicle for high productivity crops, as it carries the genetic potential and technology necessary for the success of a crop. For this reason, it is considered the main input in the implementation of a crop. The objective of this work was to evaluate the influence of seed treatment with Cruiser Opti insecticide associated with the biostimulant EpívioTM at different dosages and during 0, 60, 90, 135 and 180 days after seed treatment. Rice seeds of the cultivar IRGA 424 RI were used. The treatments were: Control: Permit + Standk + Gaucho, T2- Cruiser Opti (0.5 L/100 Kg of seeds), T3 - EpivioTM (0.1 L/100 Kg of seeds), T4 - Cruiser Opti + EpivioTM (0.5 + 0.05 L/100 kg of seeds), T5 - Cruiser Opti + EpivioTM (0.5 + 0.1 L/100 kg of seeds) and T6 – (0.5 + 0.2 L/100 kg of seeds). Seed quality was monitored through the germination test, cold test and emergence in trays. Under the conditions in which the work was carried out, we can conclude that the treatment composed of Cruiser Opti + EpivioTM, at a dose of 0.5 + 0.1 L/100Kg of seeds, respectively, provided better performance in the germination test in the evaluated periods when compared to the other treatments.